Respostas
respondido por:
4
X^3 + 2x^2 + 7x + 14=
X^3 + 2x^2 + 7 (X + 2)=
X^2 (x + 2) + 7 (X + 2)=
(X + 2)(x^2 + 7)
X^3 + 2x^2 + 7 (X + 2)=
X^2 (x + 2) + 7 (X + 2)=
(X + 2)(x^2 + 7)
respondido por:
2
Bom dia!
Podemos fatorar toda a expressão, pois há termos em comum:
x³ + 2x² + 7x + 14 = x(x² + 2x + 7) + 14
Podemos fatorar toda a expressão, pois há termos em comum:
x³ + 2x² + 7x + 14 = x(x² + 2x + 7) + 14
Anônimo:
me bajude ne
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás